2018
DOI: 10.1016/j.jcma.2018.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of the peptic ulcer bleeding in aging uremia patients under regular hemodialysis

Abstract: Aging HD patients are associated with higher risk of PUB. The use of NSAIDs and corticosteroids and co-morbidities including DM, history of uncomplicated PUD, and cirrhosis were identified as risk factors for PUB in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…75 Severely ill and people with chronic illness, whereas aging hemodialysis patients had significantly higher incidences of PUB than the matched controls. 64 And also co morbidity in patients diagnosed with hypoalbuminemia has a significantly elevated risk of developing PUB.…”
Section: Discussionmentioning
confidence: 99%
“…75 Severely ill and people with chronic illness, whereas aging hemodialysis patients had significantly higher incidences of PUB than the matched controls. 64 And also co morbidity in patients diagnosed with hypoalbuminemia has a significantly elevated risk of developing PUB.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies revealed an increased susceptibility to major bleeding events in dialysis patients [320,321]. Potential etiologies include platelet dysfunction, dysfunctional von Willebrand factor, decreased production of thromboxane, uremic toxins, and anemia [322,323].…”
Section: Uremic Coagulopathymentioning
confidence: 99%
“…Studies report that patients with end-stage renal disease (ESRD), through a cluster of complex pathophysiological mechanisms, are at a higher risk of bleeding peptic ulcers than the general population [ 6 , 7 ]. A higher rate of hemodialysis utilization, which is independently associated with a higher occurrence of PUB, has also been reported in the US population and may amplify the rate of PUB [ 7 ].…”
Section: Introductionmentioning
confidence: 99%